Histone Deacetylase Inhibitors to Overcome Resistance to Targeted and Immuno Therapy in Metastatic Melanoma - Yeon, Minjeong; Kim, Youngmi; Jung, Hyun Suk; Jeoung, Dooil (Frontiers in Cell and Developmental Biology, 2020)
Therapies that target oncogenes and immune checkpoint molecules constitute a major group of treatments for metastatic melanoma. A mutation in BRAF (BRAF V600E) affects various signaling pathways, including mitogen activated protein kinase (MAPK) and PI3K/AKT/mammalian target of rapamycin (mTOR) in melanoma. Target-specific agents, such as MAPK inhibitors improve progression-free survival. However, BRAFV600E mutant melanomas treated with BRAF kinase inhibitors develop resistance. Immune checkpoint molecules, such as programmed death-1 (PD-1) and programmed death ligand-1(PD-L1), induce immune evasion of cancer cells. MAPK inhibitor resistance results from the increased expression of PD-L1. Immune checkpoint inhibitors, such as anti-PD-L1 or anti-PD-1, are main players in immune therapies designed to target metastatic melanoma. However, melanoma patients show low response rate and resistance to these inhibitors develops within 6-8 months of treatment. Epigenetic reprogramming, such as DNA methylaion and histone modification, regulates the expression of genes involved in cellular proliferation, immune checkpoints and the response to anti-cancer drugs. Histone deacetylases (HDACs) remove acetyl groups from histone and non-histone proteins and act as transcriptional repressors. HDACs are often dysregulated in melanomas, and regulate MAPK signaling, cancer progression, and responses to various anti-cancer drugs. HDACs have been shown to regulate the expression of PD-1/ PD-L1 and genes involved in immune evasion. These reports make HDACs ideal targets for the development of anti-melanoma therapeutics. We review the mechanisms of resistance to anti-melanoma therapies, including MAPK inhibitors and immune checkpoint inhibitors. We address the effects of HDAC inhibitors on the response to MAPK inhibitors and immune checkpoint inhibitors in melanoma. In addition, we discuss current progress in anti-melanoma therapies involving a combination of HDAC inhibitors, immune checkpoint inhibitors, and MAPK inhibitors.